Characteristics of theses Characteristics of theses for physician graduation: a cross-sectional study in Peru - Angulo-Fernandez, Kevyn Javier (2023)
Introduction Research in Peru presents several barriers that impede its development and that also affects the theses to graduate as physician. Our objective was to characterize the theses for obtaining a medical degree in Peru. Methods An observational and descriptive study evaluating the theses for obtaining a medical degree of 2019, evaluated in January 2022 from 22 universities that are full members of the Peruvian Association of Faculties of Medicine. Characteristics of the universities and theses were evaluated, including the evaluation of a institutional research ethics committee , the aligment with a national research priority, and publication status in a scientific journal. The absolute and relative frequencies of the study variables were described. Results A total of 1838 theses were evaluated. Most of the theses were written by a single student (66.16%). The most common study design was the descriptive cross-sectional type (42.33%). We found that 53.86% of the theses responded to a national research priority, the most common being “maternal, perinatal and neonatal health“ (26.01%). Of the total, 56.75% did not indicate whether they had the approval of an institutional research ethics committee. Only 40 theses (2.19%) were published in a scientific journal (14 in indexed journals). Conclusion Two-thirds of the theses conducted by medical students in Peru are descriptive studies. Half respond to national research priorities. Four out of ten theses were approved by an institutional research ethics committee. The number of published theses is low. The results show shortcomings in university institutional policies that encourage ethical compliance and research development.